Effects of different sterilization methods on milk quality: a comparative analysis - Ruoqian Shi; Ying Gu; Qi Zhang; Yangyue Ding; Xuejing Fan (Food Science of Animal Products, 2025)
Milk is rich in high-quality protein, calcium, and various vitamins and minerals, which are crucial for bone health, immune regulation, and metabolic functions. In the food industry, milk is not only the basic raw material for liquid dairy products but also, through advanced processing techniques, has led to the development of more valuable new products such as infant formula and functional dairy products. However, during harvesting, processing, storage, and transportation, milk can become contaminated by microorganisms, which can significantly affect its quality and shelf life. Effective sterilization is crucial for maintaining the nutritional quality and extending the shelf life of milk. While traditional heat treatments are effective at inactivating harmful microorganisms, they often result in nutrient loss due to high temperatures. As a result, emerging technologies, including both thermal and non-thermal methods, have been developed to address these challenges. Emerging thermal processing technologies can achieve rapid and uniform heating, significantly reducing processing time. Non-thermal processing technologies, on the other hand, directly act on microorganisms through physical fields, enabling efficient sterilization without the need for high temperatures. Both methods better preserve the nutritional components and natural flavors of milk and are particularly suitable for sterilizing high-viscosity, particulate-containing, or heat-sensitive foods. This paper provides a comprehensive overview of the characteristics of traditional heat-based sterilization methods, newer thermal processing technologies, and non-thermal methods. It also discusses the impact of different processing technologies on milk’s nutritional content and offers an outlook on future developments, with the aim of providing valuable insights for the improvement of milk sterilization technologies.